The ‘Missing Middle’: Landscape Restoration’s Greatest Challenge - Minang, Peter A.; Anulisa, C.O.; Wainaina, P.; Duguma, L.A.; Guariguata, Manuel R. (CIFOR-ICRAF, 2021)
The world urgently needs to restore huge swaths of land to meet the demand for ecosystem services and is targeting 350 M Ha by 2030 under the New York Declaration on Forests and the Bonn Challenge. Tremendous resources - financial, human and other - are needed at international, national, sub-national and local levels. International mobilization has been great so far. National awareness and commitments are also robust. Many excellent local success stories have also been reported. However, for scaling up and implementing restoration, a critical mass of involvement of sub-national governments, local NGOs, CBOs, academia, and enterprise is needed. So far, evidence of engagement of this key cohort is thin, and this missing meso level engagement may well be restoration’s number one challenge. This is what this policy brief seeks to address.